Glycogen Synthase Kinase 3 Gene Is Important in Growth and Molting of the Pacific White Shrimp Litopenaeus vannamei - Pang, Ying; Zhang, Xiaojun; Yuan, Jianbo; Zhang, Xiaoxi; Su, Manwen; Li, Fuhua (Frontiers in Marine Science, 2021)
Glycogen synthase kinase 3 (GSK3) is a vital multifunctional molecule that is widely distributed in invertebrates and vertebrates. GSK3 is a highly conserved serine/threonine (Ser/Thr) protein kinase, which plays an important role in insulin, Wnt, and various signaling pathways. In this study, a GSK3 gene were identified in the genome of the Pacific white shrimp, Litopenaeus vannamei, and analyzed its gene structure, phylogeny, and expression profiles. The deduced LvGSK3 protein contains a highly conserved Ser/Thr protein kinase catalytic (S_TKc) domain, the LvGSK3 gene exhibited high expression in different early developmental stages, most adult tissues, and premolting stages. RNA interference of LvGSK3 significantly retarded the increment of body weight and affected the expressions of molting-related genes compared with control groups. These results will improve our understanding of the conserved structure and functions of the LvGSK3 gene and show potential applications of shrimp growth.